ANALISIS SEMIOTIK DALAM KOMIK STRIP KONPOPILAN - Aviolis, Maura; Patriantoro, Patriantoro; Syahran, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â AbstractThe Konpopilan strip comics have their own peculiarities in conveying the story content that follows the things that happen in life, because it is does not use the language symbol on the dialogue. This research uses descriptive method with qualitative research form. Mean sign data was analysed by triadic technique of Pierce theory. The strip comic data is understood by the visual language technique of drawing. Conversational implicature data is analysed by Grice theory, i.e. conventional implicature. Strip comic data is culturally interpreted with cultural context analysis techniques. The result of data analysis concluded that the meaning of the signs can be found: character; behaviour; text balloon; punctuation; line; and the environment, with a total of 842 signs. Visual language can be described in the form of narrative that the flow of each scene is connected. There are 22 that have a single conversation implicature, one that have two conversation implicatures, and one comic strip that no conversation implicature is found. Comic strip writer Konpopilan made the news ever published into a comic strip story Konpopilan and divided into four sections. Keywords: semiotic, implicature, comic, visual language, sign.